Peran Kepemimpinan Dalam Penguatan Keyakinan (Sradha) Umat Buddha Di Desa Tanjung Kabupaten Jepara - Darma, Widia; Suyatno, Tri; Siswoyo, Eko (Kamaya: Jurnal Ilmu Agama, 2024)
Leadership plays a crucial role in achieving shared goals, especially within Buddhist organizations in Tanjung Village, Monastery leaders are not only responsible for resource management but also serve as spiritual role models, motivators, and facilitators for the community. At Monastery, leadership is guided by principles of cooperation, transparency, and openness, encouraging active participation in various religious activities. The influence of social challenges and modern technology has affected the involvement of the younger generation in religious practices. Adaptive leadership is essential to maintain the community’s spiritual vitality and strengthen their faith in Buddhist teachings. By implementing values-based leadership, leaders can foster spiritual harmony, bolster solidarity, and ensure the continuity of Buddhist practices in facing modern challenges. This study employs a descriptive qualitative method to explore the role of leadership in educating Buddhists in Tanjung Village. The findings highlight that monastery leaders play a critical role in goal setting, work planning, and resource management. Leadership practices based on openness, togetherness, and cooperation enable Buddhists to participate voluntarily in decision-making and task division, thereby fostering a sense of responsibility and social solidarity within the community. Additionally, monastery leaders serve as exemplary figures in religious services and facilitators who connect the community with spiritual activities. They contribute to the development of the younger generation through education, arts, culture, and religious programs that enhance Buddhist faith. With their dual roles as administrators and spiritual guides, monastery leaders ensure the preservation of Buddhist teachings and the sustainability of the community, helping Buddhists adapt and societal dynamics.